Genotype-Specific Incidence and Clearance of Human Papillomavirus in Oral Mucosa of Women: A Six-Year Follow-Up Study - Louvanto, Karolina (Public Library of Science, 2013)
BACKGROUND: There are no previous longitudinal studies on genotype-specific natural history of human papillomavirus (HPV) infections in oral mucosa of women. METHODS: In the Finnish Family HPV Study, 329 pregnant women were enrolled and followed up. HPV-genotyping of oral scrapings was performed with nested PCR and Multimetrix® test (Progen, Heidelberg, Germany). Incidence and clearance times and rates for each HPV-genotype identified in oral mucosa were determined. Predictors for incident and cleared HPV infections for species 7/9 genotypes were analyzed using Poisson regression model. RESULTS: Altogether, 115 baseline HPV-negative women acquired incident oral HPV infection, and 79 women cleared their infection. HPV16 and multiple HPVs most frequently caused incident infections (65% and 12%) in 13.3 and 17.1 months respectively, followed by HPV58, HPV18 and HPV6 (close to 5% each) in 11–24 months. HPV58, HPV18 and HPV66 were the most common to clear. HPV6 and HPV11 had the shortest clearance times, 4.6 months and 2.5 months, and the highest clearance rates, 225.5/1000 wmr and 400/1000 wmr, respectively. The protective factors for incident oral HPV-species 7/9 infections were 1) new pregnancy during follow-up and 2) having the same sexual partner during FU. Increased clearance was related with older age and a history of atopic reactions, whereas previous sexually transmitted disease and new pregnancy were associated with decreased clearance. CONCLUSIONS: HPV16 was the most frequent genotype to cause an incident oral HPV-infection. Low risk HPV genotypes cleared from oral mucosa more quickly than high risk HPV genotypes. Pregnancy affected the outcome of oral HPV infection.